2022
DOI: 10.1016/j.isci.2021.103672
|View full text |Cite
|
Sign up to set email alerts
|

Integrated miRNA/cytokine/chemokine profiling reveals severity-associated step changes and principal correlates of fatality in COVID-19

Abstract: Inflammatory cytokines and chemokines (CC) drive COVID-19 pathology. Yet, patients with similar circulating CC levels present with different disease severity. Here, we determined 171 microRNAomes from 58 hospitalised COVID-19 patients (Cohort 1) and levels of 25 cytokines and chemokines (CC) in the same samples. Combining microRNA (miRNA) and CC measurements allowed for discrimination of severe cases with greater accuracy than using miRNA or CC levels alone. Severity group-specific associations between miRNAs … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 64 publications
6
34
0
Order By: Relevance
“…Secondly, most of the miRNAs associated with severe COVID-19 were found to be downregulated. This is in agreement with a recent study where a paralleled downregulation of miRNA expression in severe COVID-19 was reported [47]. Bartoszewski et al suggested that the SARS-CoV-2 genome acts as miRNA sponge to reduce cellular miRNA levels [48].…”
Section: Discussionsupporting
confidence: 92%
“…Secondly, most of the miRNAs associated with severe COVID-19 were found to be downregulated. This is in agreement with a recent study where a paralleled downregulation of miRNA expression in severe COVID-19 was reported [47]. Bartoszewski et al suggested that the SARS-CoV-2 genome acts as miRNA sponge to reduce cellular miRNA levels [48].…”
Section: Discussionsupporting
confidence: 92%
“…A paralleled down‐regulation of miRNA expression in severe COVID‐19 was reported lately. 1 RNA silencing pathways have been identified as antiviral defense mechanisms in plants and insects, and possibly in mammalian cells. 2 To escape this antiviral defense, plant and insect viruses possess virus‐encoded suppressors of RNA interference, and this may extend to mammalian cells.…”
Section: Figurementioning
confidence: 99%
“…Their results have indicated that miR-30b/c/e, miR-6080, miR-181a-5p, miR-199a-3p, and miR-339 are highly specific for determination of severity and mortality rate of COVID-19 ( Gustafson et al, 2022 ). In addition, Wilson et al have shown correlations between levels of CCL20, IL-6, IL-10, and miR-451a and mortality of COVID-19 patients ( Wilson et al, 2022 ). Besides, miR-133a and miR-122 have been found to be correlated with 28 day mortality of COVID-19 patients.…”
Section: Dysregulated Mirnas In Covid-19mentioning
confidence: 99%